A qualitative study of the spirituality of volunteers registered for human organ donation - Yueyan Zhao; Qunfang Miao; Lingjing Qiu; Tingting Hu (BMC Medical Ethics)
Abstract Background Exploring the spiritual cognition of human organ donation registration volunteers, aiming to provide new ideas for promoting the development of organ donation through this perspective. Methods This qualitative research was conducted following the conventional content analysis method. 10 registered volunteers for human organ donation were selected from July to December 2023 for face-to-face semi-structured interviews. Snowball sampling was employed to select the participants. In-depth semi-structured interviews were conducted for data gathering. Theoretical saturation was achieved through 10 interviews. Colaizzi phenomenological 7-step analysis method was used to analyze the interview content. Results The spirituality of registered volunteers for human organ donation can be summarized into three themes and seven sub themes: ① Spiritual Understanding (Love & Life Extension, Dedication to society, Death elevates life); ② The Supporting Role of Spirituality (Become a spiritual motivation for a better life, self-transcendence ); ③ The Spiritual Emotional Value of Organ Donation (Sense of accomplishment and pride, Sense of complexity and ambivalence). Conclusion The willingness to donate organs is closely related to spirituality. By understanding the spirituality of this group, it is possible to take an important step in promoting the development of organ donation.